Effects of pre-mix herbicide combinations on weed management in transplanted rice (Oryza sativa) - SAIKIA, NILUTPAL; SINGH, MANOJ KUMAR; POONIYA, VIJAY; GOVINDASAMY, PRABHU; AAKASH; DENDUKURI, UDAYA LAKSHMI; NITHINKUMAR, KADAGONDA; BAGRECHA, SHREYAS; ALI, S K ASRAFUL; PRAJAPATI, SUNIL KUMAR (The Indian Journal of Agricultural Sciences, 2024)
An experiment was conducted during rainy (kharif) season of 2021 at the Agricultural Farm of Banaras Hindu University, Varanasi, Uttar Pradesh for evaluating the efficacy of pre-mix herbicide combinations applied as post emergence in managing weeds in transplanted rice. We assessed 9 different weed management treatments, including sole herbicide and pre-mix combinations and hand weeding in randomized block design. Results showed that herbicide combinations such as triafamone + ethoxysulfuron and bispyribac sodium + pyrazosulfuron effectively reduced weed density and biomass, improving crop growth attributes and ultimately yield. The study highlights the importance of using herbicide combinations for effective weed management in puddle-transplanted rice cultivation.